Disorder-induced localization in crystalline phase-change materials - Siegrist, T.; Jost, P.; Volker, H.; Woda, M.; Merkelbach, P.; Schlockermann, C.; Wuttig, M. (Nature materials, 2011)
Localization of charge carriers in crystalline solids has been the subject of numerous investigations over more than half a century. Materials that show a metal–insulator transition without a structural change are therefore of interest. Mechanisms leading to metal–insulator transition include electron correlation (Mott transition) or disorder (Anderson localization), but a clear distinction is difficult. Here we report on a metal–insulator transition on increasing annealing temperature for a group of crystalline phase-change materials, where the metal–insulator transition is due to strong disorder usually associated only with amorphous solids. With pronounced disorder but weak electron correlation, these phase-change materials form an unparalleled quantum state of matter. Their universal electronic behaviour seems to be at the origin of the remarkable reproducibility of the resistance switching that is crucial to their applications in non-volatile-memory devices. Controlling the degree of disorder in crystalline phase-change materials might enable multilevel resistance states in upcoming storage devices. Phase-change materials are used in computer memories for their switching between amorphous and crystalline phases. However, even the crystalline state shows disorder, with extremely small electron mean free paths. The discovery that, depending on annealing temperature, this disorder leads to a metal–insulator transition in the crystalline phase provides a completely new look at the transport properties of these compounds.